2018
DOI: 10.4995/eurocall.2018.7947
|View full text |Cite
|
Sign up to set email alerts
|

Web 2.0 tools in the EFL classroom: Comparing the effects of Facebook and blogs on L2 writing and interaction

Abstract: Web 2.0 technologies have become an integral part of our lives, transforming not only how we communicate with others, but also how language is taught and learned in the L2 classroom. Several studies have looked into the use of these tools and how they influence L2 learning (e.g. Jin, 2015;Wang & Vásquez, 2014), yet only one has compared the effects of two Web 2.0 technologies (Castaneda Vise, 2008). Thus, the aim of this study was to compare the impact that Facebook and blogs had on the writing skills, namely,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…Concerning L2 pedagogy, blogs have recently attracted much research attention (e.g., Alm, 2009;Bakar & Ismail, 2009;Ducate & Lomicka, 2005;Lee, 2009;Murray & Hourigan, 2008;Zhang, 2009). As far as L2 writing is concerned, various scholars have corroborated the usefulness of blogs for enhancing writing competencies (Armstrong & Retterer, 2008;Dizon & Thanyawatpokin, 2018;Fathi & Nourzadeh, 2019;Nguyen, 2012;among others). The effectiveness of blogs in L2 writing is usually associated to their potentials in providing the users with access to the links of other online resources, encouraging further writing practice, providing a real audience to write for, increasing cooperation, fostering autonomous learning, shaping a sense of ownership, building a sense of community, improving learner engagement, and promoting further feedback (Campbell, 2003(Campbell, , 2005Chen, 2016;Fathi & Nourzadeh, 2019;Fathi & Rahimi, 2020;Fellner & Apple, 2006;Nguyen, 2012;Kusumaningrum, Cahyono, & Prayogo, 2019;Rahimi & Fathi, 2021;.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning L2 pedagogy, blogs have recently attracted much research attention (e.g., Alm, 2009;Bakar & Ismail, 2009;Ducate & Lomicka, 2005;Lee, 2009;Murray & Hourigan, 2008;Zhang, 2009). As far as L2 writing is concerned, various scholars have corroborated the usefulness of blogs for enhancing writing competencies (Armstrong & Retterer, 2008;Dizon & Thanyawatpokin, 2018;Fathi & Nourzadeh, 2019;Nguyen, 2012;among others). The effectiveness of blogs in L2 writing is usually associated to their potentials in providing the users with access to the links of other online resources, encouraging further writing practice, providing a real audience to write for, increasing cooperation, fostering autonomous learning, shaping a sense of ownership, building a sense of community, improving learner engagement, and promoting further feedback (Campbell, 2003(Campbell, , 2005Chen, 2016;Fathi & Nourzadeh, 2019;Fathi & Rahimi, 2020;Fellner & Apple, 2006;Nguyen, 2012;Kusumaningrum, Cahyono, & Prayogo, 2019;Rahimi & Fathi, 2021;.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the target group performed better than the other group in terms of accuracy and quality in writing. Furthermore, Dizon and Thanyawatpokin (2018) tried to compare the implementation of Facebook and blogs on writing skill with regard to syntactic complexity, lexical variety and fluency at a Japanese EFL context. The results showed that blogging was more influential in promoting of EFL writing and the students had more favorable attitudes towards blogging in EFL writing than the students in Facebook group.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Web technologies gained an indispensable part not only in daily life but also in education contexts by offering learners a variety of learning opportunities and professionals can benefit from their advantages by employing Web 2.0 tools in education contexts (Arslan, 2018;Dizon & Thanyawatpokin, 2018;Hurlburt, 2008;Li, Bado, Smith, & Moore, 2013). Web 2.0 tools can be very valuable especially in foreign/second language writing classes.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, CMC in both synchronous and asynchronous types has had positive and significant effects on L2 development. Some studies researched skills of writing, reading and syntactic complexity in language education (Dizon and Thanyawatpokin, 2018;Li, 2012;Hsu, 2015) as well as the development of speaking skills and pronunciation of target languages (Correa, 2015;Alastuey, 2010;Lee, 2007). In addition, other studies focused on intercultural competence improvement using CMC such as Skype, teleconferencing tools, or online forums (Godwin-Jones, 2013;Wilden, 2007;Wu, 2018).…”
Section: The Effects Of Computer-mediated Communication On Linguistic and Intercultural Competencementioning
confidence: 99%
“…"A wiki was developed approximately in 1995 as a part of Web 2.0 -the read/write web (p.17)", so it has been used to develop students' skills of reading and writing. Dizon and Thanyawatpokin (2018) also argued that the Web 2.0 tools were found to have equally positive and significant effects on writing fluency and syntactic complexity, while neither CMC method had any effect on lexical richness. In language education, Computer-Mediated Communication (CMC) and telecollaboration using tools such as Wikis have many possibilities for students' development of four skills of a target language and intercultural communicative competence through communication with people by using the target language.…”
Section: Introductionmentioning
confidence: 98%